1994
DOI: 10.3382/ps.0730259
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Laying Hens to Diets Containing up to 2% DL-Methionine or Equimolar (2.25%) 2-Hydroxy-4-(Methylthio)Butanoic Acid

Abstract: Diets supplemented with up to .6% DL-Met (DLM) or .68% 2-hydroxy-4-(methylthio)butanoic acid (HMB, Alimet) acidify the urine and reduce the incidence of urolithiasis in pullets and laying hens. Excessive acidification potentially may reduce eggshell quality and bone mineralization by interfering with Ca metabolism and may severely challenge the liver and kidneys, which are the primary organs responsible for attenuating metabolic acidosis. To evaluate these possibilities, 30-wk-old Single Comb White Leghorn hen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

1994
1994
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
0
5
1
Order By: Relevance
“…This may be the main reason there was no effects of methionine source and level on egg production performance of broiler breeder hens and no deficient symptom for hens fed basal diets. Adding methionine at 1% (from HMTBA or DLM) did not suppress the production performance of broiler breeders in the present study, which was not in line with those reports by Xie et al (2007) and Wideman et al (1994). Adding DLM at 1% or HMTBA at 1.13% by Xie et al (2007) reduced average daily feed intake (ADFI) of ducks to 207.6 g/ bird/day or 224.1 g/bird/day, respectively, but the ADFI was higher than that of broiler breeders in the present study (130 g/bird/day at peak).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This may be the main reason there was no effects of methionine source and level on egg production performance of broiler breeder hens and no deficient symptom for hens fed basal diets. Adding methionine at 1% (from HMTBA or DLM) did not suppress the production performance of broiler breeders in the present study, which was not in line with those reports by Xie et al (2007) and Wideman et al (1994). Adding DLM at 1% or HMTBA at 1.13% by Xie et al (2007) reduced average daily feed intake (ADFI) of ducks to 207.6 g/ bird/day or 224.1 g/bird/day, respectively, but the ADFI was higher than that of broiler breeders in the present study (130 g/bird/day at peak).…”
Section: Discussioncontrasting
confidence: 99%
“…Adding DLM at 1% or HMTBA at 1.13% by Xie et al (2007) reduced average daily feed intake (ADFI) of ducks to 207.6 g/ bird/day or 224.1 g/bird/day, respectively, but the ADFI was higher than that of broiler breeders in the present study (130 g/bird/day at peak). ADFI of commercial laying hens was significantly reduced by adding DLM at 1% or HMTBA at 1.13% when compared with the control group (Wideman et al 1994). These results showed that broiler breeders can tolerate a higher methionine level than commercial laying hens.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…On the other hand, feed intake was not affected by a range of dietary ME from 2400 to 2900 kcal ME/kg (Adeyemo and Longe, 1996). Depression in feed intake is a highly sensitive response to excessive amino acid supplementation because diets supplemented with 0.10% DL-methionine significantly reduced feed intake (Wideman et al 1994).…”
Section: Feed Intake and Feed Conversionmentioning
confidence: 99%
“…6% (egg weight) with the exponential model, and was 89.7% (egg production), 89.6% (egg mass), and 86.8% (egg weight) with the slope-ratio model. However, several researchers reported that there was no difference in bioefficacy between DLM and HMB (Reid et al, 1982;Harms and Russell, 1994;Wideman et al, 1994). In broiler chickens, moreover, we have concluded that as long as TSAA requirement is set at the commercial or maximal requirement, bioefficacy of HMB relative to DLM on a weight basis seems to be 88% Bunchasak, 2009).…”
Section: Introductionmentioning
confidence: 91%